Partner violence against women with malignancies - Klikovac Tamara (Temida)
The content of this paper is an overview of the results of some available foreign studies related to the experience of violence against women suffering from various malignancies, especially breast and gynecological cancers. The topic is both specific and complex because it considers double victimization - malignancy and violence. The idea for this review paper emerged from author’s observations during the years of her clinical and psychotherapy practice, who after 16 years of work with the population of children, adolescents and adults with malignant diseases at the Institute of Oncology and Radiology of Serbia, continued to deal with counseling and psychotherapy of adult oncology patients and their family members in private practice. This paper is intended to stimulate research on violence against women suffering from malignant diseases in Serbia. The author’s experience and observations from her daily psychotherapy practice indicate that violence, especially partner violence against women suffering from malignant diseases, both in the years before the onset of the disease and during and after the end of combined oncological treatment, is, unfortunately, rather present in Serbia. For a more comprehensive and systematic insight into this issue, it is necessary to conduct an “anonymous” national victimization survey to cover women aged 19-75 who are treated for the most common malignancies typical for women (breast and gynecological cancers) in all reference national oncology centers across Serbia.